Factors affecting export demand for the Malaysian rubber products - Syarifa, Lina Fatayati (2009)
Rubber products have greatly contributed to the export earning of Malaysia. However, the export demands for Malaysian rubber products have been fluctuating over the years. The fluctuation in the quantity demanded for Malaysian rubber products export is caused by several factors such as the export price of the rubber products, foreign income, and the price of substitute. This study was an attempt to determine the factors which have significantly affected the export demand for the rubber products in the short term. In order to accomplish the objective of the study, the Error Correction Model (ECM) was employed. The secondary data (quarterly) gathered from 1998 to 2007 were used in this study. The variables include the quantity of the export rubber products, export price of the rubber products, Gross Domestic Product (GDP) per capita of Organization for Economic Co-operation and Development (OECD) (used as a proxy of the world’s income), and the synthetic rubber price as a substitute price. Before the estimation of regression was done, each individual series (both in levels and first differences) was tested for their unit roots, using the Augmented Dickey Fuller (ADF) and Philip Peron (PP) Tests. The results gathered from the unit root tests showed that all the variables used in the study were integrated with the order of one, or I (1). The next step was to determine whether any combinations of the variables were co-integrated in the long run, using the multivariate co-integration test of Johansen and Juselius on each of the five equations. The results revealed that all the variables of the export demand for the rubber products were co-integrated in the order of one, or I (1). Therefore, this enabled the researcher to implement the ECM test. The results from the estimation of the ECM showed that in the midstream rubber products, the own price elasticity of latex concentrate and Standard Malaysian Rubber (SMR 20) were inelastic with an elasticity of 0.98 and 0.20, respectively. Meanwhile, the income elasticity of the SMR 20 is 0.29, implying that the SMR 20 could be considered as necessity goods. In particular, the income elasticity of latex concentrate is 2.95, indicating that latex concentrate could also be considered as luxury goods. Cross price elasticity of the latex concentrate and SMR 20 were found to be inelastic with their cross price elasticity of 0.08 and 0.21, respectively, and they possessed positive sign which showed that the latex concentrate and SMR 20 were substitution for synthetic rubber. In downstream rubber products, the own price elasticity of glove is elastic with its own price elasticity of 1.14, and become important determinant of export demand. However, the own price elasticity of latex threads and motorcar tyre are found to be inelastic with their own price elasticity of 0.11 and 0.79 respectively. The income elasticity of glove was found to be 0.51, implying that it could be considered as necessity goods. Meanwhile, the income elasticity of latex threads and motorcar tyre was 1.00, and 7.46, respectively, indicating that latex threads and motorcar tyre could be considered as luxury goods. Nevertheless, the cross price elasticity of glove and latex threads was found inelastic against synthetic rubber which was 0.06 and 0.06, respectively. Coupled with the positive sign, both glove and latex threads were proven as substitute products for synthetic rubber. The income elasticity of motorcar tyre was found to be elastic against synthetic rubber, i.e. 1.37, and it had negative sign which indicated that motorcar tyre was complementary for synthetic rubber. In relation to the midstream rubber industry, the findings of this study suggest that Malaysia should emphasize more on supply management policy actions. In more specific, the policy in own price and the price of synthetic rubber in the midstream rubber industry will not impose important effect for the demanded export quantity. As for the rubber downstream industry, the government should intensify research and development (R&D) activities to ensure that all Malaysian rubber products meet international standards in health and safety. In particular, the improvement in terms of price competitiveness would be an appropriate strategy if Malaysia were to increase its export growth for glove. This could be achieved by reducing the cost incurred in producing gloves. One of the downstream rubber products is complementary with synthetic rubber. Therefore, the policy that should be taken is reducing the production cost of synthetic rubber. This policy has been implemented by the Malaysian Government, i.e. by removing the import duty imposed on synthetic rubber in 1986.